2020
DOI: 10.4236/msa.2020.111001
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Proton Conductivity in Chitin-Chitosan Mixed Compounds

Abstract: In order to investigate a key factor for the appearance of proton conductivity in chitin-chitosan mixed compounds, the chitin-chitosan mixed compounds (chitin) x (chitosan) 1−x were prepared and these proton conductivities have been investigated. DC proton conductivity 0 σ is obtained from Nyquist plot of impedance measurement data, and the relationship between 0 σ and mixing ratio x has been made clear. It was found that the x dependence of 0 σ is non-monotonous. That is, 0 σ shows the anomalous behavior, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Recently, chitin and chitosan have been used in cancer treatment as a vehicle for delivering cancer drugs to a specific site and in tissue/organ regeneration and repair [5,6]. Furthermore, it has been reported that the hydrated chitin and chitosan films in humidified conditions become proton conductors similar to other biomaterials [7][8][9][10][11][12][13][14][15], and that can be used as the fuel cell electrolyte where the chemical energy by hydrogen and oxygen is directly extracted as electric energy. Thus, chitin and chitosan are versatile and have the potential to play an important role in a wide range of industries, and are the most attractive biomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, chitin and chitosan have been used in cancer treatment as a vehicle for delivering cancer drugs to a specific site and in tissue/organ regeneration and repair [5,6]. Furthermore, it has been reported that the hydrated chitin and chitosan films in humidified conditions become proton conductors similar to other biomaterials [7][8][9][10][11][12][13][14][15], and that can be used as the fuel cell electrolyte where the chemical energy by hydrogen and oxygen is directly extracted as electric energy. Thus, chitin and chitosan are versatile and have the potential to play an important role in a wide range of industries, and are the most attractive biomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Under humid conditions, chitosan is known to become a proton conductor, as in the case of other biomaterials [ 6 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Our previous studies have also shown that hydrated chitosan containing a low water content at 298K exhibits a high proton conductivity as the water content increases [ 24 , 25 , 26 , 27 ], which indicates that the hydration water plays an important role in proton conduction. However, in the context of proton conductivity, no microscopic investigation has been carried out into the role of water molecules bonded to the main chain.…”
Section: Introductionmentioning
confidence: 99%